2019
DOI: 10.1242/dev.175497
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 defines apical identity and regulates epithelial morphogenesis by promoting apical recruitment of Par6-aPKC and Crumbs

Abstract: Cdc42 regulates epithelial morphogenesis together with the Par complex (Baz/Par3-Par6-aPKC), Crumbs (Crb/CRB3) and Stardust (Sdt/PALS1). However, how these proteins work together and interact during epithelial morphogenesis is not well understood. To address this issue, we used the genetically amenable Drosophila pupal photoreceptor and follicular epithelium. We show that during epithelial morphogenesis active Cdc42 accumulates at the developing apical membrane and cell-cell contacts, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 69 publications
2
24
0
Order By: Relevance
“…We also found that depletion of PAR-3 from the epidermis resulted in a partial loss of PAR-6. This is consistent with findings that multiple mechanisms can promote cortical recruitment of Par6-aPKC, including binding of Par6 to Par3 or Cdc42, and binding of aPKC to phospholipids (Dong et al, 2020;Hong et al, 2003;Hutterer et al, 2004;Joberty et al, 2000;Nagai-Tamai et al, 2002;Nunes de Almeida et al, 2019;Rodriguez et al, 2017;Wang et al, 2017;Wodarz et al, 2000). Conversely, the apical localization of PAR-3 was dependent upon PKC-3.…”
Section: Interdependencies Between the Par Proteinssupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that depletion of PAR-3 from the epidermis resulted in a partial loss of PAR-6. This is consistent with findings that multiple mechanisms can promote cortical recruitment of Par6-aPKC, including binding of Par6 to Par3 or Cdc42, and binding of aPKC to phospholipids (Dong et al, 2020;Hong et al, 2003;Hutterer et al, 2004;Joberty et al, 2000;Nagai-Tamai et al, 2002;Nunes de Almeida et al, 2019;Rodriguez et al, 2017;Wang et al, 2017;Wodarz et al, 2000). Conversely, the apical localization of PAR-3 was dependent upon PKC-3.…”
Section: Interdependencies Between the Par Proteinssupporting
confidence: 91%
“…In mature epithelia, however, the bulk of Par3 segregates to the apical/lateral border, where it plays an essential role in the positioning and assembly of apical junctions (Achilleos et al, 2010;Georgiou et al, 2008;Harris and Peifer, 2004;Harris and Tepass, 2008;Izumi et al, 1998;Leibfried et al, 2008;Totong et al, 2007;Yamanaka et al, 2001). The release of Par3 in epithelia depends on phosphorylation of Par3 by aPKC, and involves handoff of Par6-aPKC to Cdc42 and the epithelial specific Crumbs polarity complex (Bilder et al, 2003;Harris and Peifer, 2005;Hong et al, 2003;Krahn et al, 2010;Morais-de-Sá et al, 2010;Nagai-Tamai et al, 2002;Nunes de Almeida et al, 2019;Walther and Pichaud, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, at 72 hrs APF, when two distinct apical domains are distinguishable, the intersection between PIP82 and Crumbs was greatly diminished; PIP82 localized to the base of the rhabdomere while Crumbs was concentrated to the stalk membrane with some Crumbs residual staining in the rhabdomere ( Fig 3E–3H ); PIP82 colocalization with Rhodopsin 1 (Rh1) at the base of the rhabdomere suggested PIP82 is not in the microvilli but rather found in the region of the rhabdomere terminal web [ 43 ] ( S7 Fig ). Moreover, utilizing an antibody that recognizes aPKC [ 33 ], we observed a non-overlapping spatial pattern of the PIP82 and aPKC domains at one day post eclosion ( Fig 3I–3L ). In this case, PIP82 demarcates the base of the rhabdomere and aPKC the stalk membrane of each photoreceptor.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, utilizing an antibody that recognizes aPKC [33], we observed a non-overlapping spatial pattern of the PIP82 and aPKC domains at one day post eclosion (Fig 3I-3L). In this case, PIP82 demarcates the base of the rhabdomere and aPKC the stalk membrane of each photoreceptor.…”
Section: Plos Geneticsmentioning
confidence: 94%
See 1 more Smart Citation